Reliability and the service life of existing bridgers and their assessment using modern computational tools - Rudolf, Petr (Univerzita Pardubice, 2009)
The submitted dissertation deals with a modern approach of working with uncertainty - by the use of fuzzy logic for building of classification models of the technical condition evaluation of bridges objects, both their superstructure and substructure. The proposed models were validated on a data set of real bridges in operation. In the modelling process, the analysis of bridge rating methods in the Czech Republic and abroad was applied. The analysis of the amounts and shapes of input and output membership functions of given fuzzy sets was carried out, the numbers of fuzzy inference rules were determined and the appropriate choice of the defuzzification method was found out. on the basis of the achieved results, the utility of presented method of soft computing in the evaluation of the bridge technical conditions was proved.
Spolehlivost a životnost stávajících mostů a jejich hodnocení s použitím moderních výpočetních nástrojů
Keywords: hodnocení stavu mostů; výpočetní inteligence; fyzzy logika; bridge condition evaluations; soft computing; fuzzy logic